2021
DOI: 10.5056/jnm20117
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Survey of Gastroparesis in Asia by Asian Neurogastroenterology and Motility Association

Abstract: published online; they have not yet been assigned to a journal issue. When these articles are published in an issue, they will be removed. Online First articles are copy-edited, typeset and approved by the authors before publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Comment: gastroparesis (GP) is a disorder in which delayed gastric emptying occurs without any obstructive mechanism. GP is characterized by a combination of cardinal symptoms (nausea, vomiting, abdominal pain, early satiety, fullness, bloating) with no evidence of mechanical obstruction during gastroscopy, and a delayed 4-h solid-phase gastric-emptying scan [ 21 ]. Most cases of GP are idiopathic, but the disorder is also known to be associated with diabetes mellitus, gastric surgery, systemic disorders (e.g., chronic renal failure, Parkinson disease, scleroderma), drugs (e.g., opioids, anticholinergics) and viral infection [ 22 , 23 ].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…Comment: gastroparesis (GP) is a disorder in which delayed gastric emptying occurs without any obstructive mechanism. GP is characterized by a combination of cardinal symptoms (nausea, vomiting, abdominal pain, early satiety, fullness, bloating) with no evidence of mechanical obstruction during gastroscopy, and a delayed 4-h solid-phase gastric-emptying scan [ 21 ]. Most cases of GP are idiopathic, but the disorder is also known to be associated with diabetes mellitus, gastric surgery, systemic disorders (e.g., chronic renal failure, Parkinson disease, scleroderma), drugs (e.g., opioids, anticholinergics) and viral infection [ 22 , 23 ].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…In Japan, similarly to the rest of the world, underdiagnosis or challenges in diagnosis of gastroparesis in Japanese patients may stem, in part, from symptom overlap between gastroparesis and other conditions, such as functional dyspepsia, which are poorly recognized by Japanese physicians. 8 , 26 , 27 A lack of approved, effective treatment for gastroparesis has also been cited as a reason why Japanese doctors were not interested in diagnosing gastroparesis 8 ; for example, use of metoclopramide and domperidone is limited owing to safety concerns, namely, the risk of serious CNS and cardiac AEs, respectively. 28 , 29 , 30 Prior preclinical and safety pharmacology analyses have shown minimal brain penetration of trazpiroben in rats and dogs, and no clinically meaningful impacts on CNS assessments in rats following dosing up to 1000 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…There are no data for the prevalence of gastroparesis in Japan, possibly reflecting the absence of a standardized, accurate diagnostic procedure, and a poor awareness of the disease across Asia. In a recent survey of 490 physicians (including 133 physicians from Japan), half stated that they diagnosed <5 cases per year, with a quarter never diagnosing gastroparesis 8 . However, considering that approximately one‐third of patients with diabetes are thought to also have diabetic gastroparesis 5 and that the prevalence of diabetes in Japan was estimated to be 7.9% in 2010 and was predicted to rise over the coming decade, 9 there is the possibility that gastroparesis is frequently underdiagnosed in Japan.…”
mentioning
confidence: 99%
“…The prevalence of GP in Asian countries is probably lower than Western countries, or GP may have received relatively little attention in Asian countries. Recent practice survey of GP by Asian Neurogastroenterology and Motility Association reported that the reason why GP can be challenging to diagnose might be due to the lack of instrument [22].…”
Section: Discussionmentioning
confidence: 99%